Determination of the autophagic flux in murine and human peripheral blood mononuclear cells - Walter, Sophia; Jung, Tobias; Herpich, Catrin; Norman, Kristina; Pivovarova-Ramich, Olga; Ott, Christiane (Frontiers in Cell and Developmental Biology, 2023)
The autophagy lysosomal system (ALS) is crucial for cellular homeostasis, contributing to maintain whole body health and alterations are associated with diseases like cancer or cardiovascular diseases. For determining the autophagic flux, inhibition of lysosomal degradation is mandatory, highly complicating autophagy measurement in vivo. Since majority of studies focus on the autophagic flux in specific tissues, methods for prediction of systemic autophagy are limited. Within this study we provide detailed protocols for determination of the autophagic flux in peripheral blood mononuclear cells (PBMCs) isolated from human and, to our knowledge the first time, also from murine whole blood, extensively discussing advantages and disadvantages of both methods. Isolation of PBMCs was performed using density gradient centrifugation. To minimize changes on the autophagic flux through experimental conditions, cells were directly treated with concanamycin A (ConA) for 2 h at 37°C in their serum or for murine cells in serum filled up with NaCl. ConA treatment decreased lysosomal cathepsins activity and increased Sequestosome 1 (SQSTM1) protein and LC3A/B-II:LC3A/B-I ratio in murine PBMCs, while transcription factor EB was not altered yet. Aging further enhanced ConA-associated increase in SQSTM1 protein in murine PBMCs but not in cardiomyocytes, indicating tissue-specific differences in the autophagic flux in aging. In human PBMCs, ConA treatment also decreased lysosomal activity and increased LC3A/B-II protein levels. In summary, both protocols are suitable to determine the autophagic flux and may facilitate an easier detection and a better mechanistic understanding of autophagy in aging and disease models to further develop novel treatment strategies.